2019
DOI: 10.1186/s12967-019-1899-y
|View full text |Cite
|
Sign up to set email alerts
|

A robust six-gene prognostic signature for prediction of both disease-free and overall survival in non-small cell lung cancer

Abstract: Background The high mortality of patients with non-small cell lung cancer (NSCLC) emphasizes the necessity of identifying a robust and reliable prognostic signature for NSCLC patients. This study aimed to identify and validate a prognostic signature for the prediction of both disease-free survival (DFS) and overall survival (OS) of NSCLC patients by integrating multiple datasets. Methods We firstly downloaded three independent datasets under the accessing number of GSE3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 54 publications
(54 reference statements)
0
46
0
Order By: Relevance
“…To the best of our knowledge, previous studies have focused on NSCLC survival prediction, but few have examined early-stage LUAD survival prediction. However, most current prediction models are derived from clinical trials with small sample sizes [20] or single omics data [2123]. To compare the value of our proposed model, we performed a systematic review of published literature by querying PubMed using the following search terms: “((early stage) OR (stage I) OR (stage II)) AND (lung adenocarcinoma) AND (prognosis) AND ((prediction) OR (AUC) OR (c-index))” through April 29, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, previous studies have focused on NSCLC survival prediction, but few have examined early-stage LUAD survival prediction. However, most current prediction models are derived from clinical trials with small sample sizes [20] or single omics data [2123]. To compare the value of our proposed model, we performed a systematic review of published literature by querying PubMed using the following search terms: “((early stage) OR (stage I) OR (stage II)) AND (lung adenocarcinoma) AND (prognosis) AND ((prediction) OR (AUC) OR (c-index))” through April 29, 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies indicated that gene signature can well predict the prognosis of cancer. 12,13 However, no prior prognostic models for papillary thyroid carcinoma were established based on autophagy-related genes (ARGs). Therefore, the current study aimed to identify differentially expressed ARGs and build a novel prognostic signature to predict the prognosis of patients with papillary thyroid carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Differentially expressed genes (DEGs) that regulated by gene transcription are implicated in diverse biological processes. Gene-expression profiling analysis made some progresses in predicting overall survival (OS) in NSCLC [ 1 , 6 , 7 ]. Mascaux et al showed that immune activation and immune escape in tumor microenvironment (TME) occurred before lung cancer invasion [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several genes or long noncoding RNA expression signatures, including programmed death-ligand 1(PD-L1), have been recently proposed for predicting the OS in NSCLC [ 6 , 8 10 ], the prognostic value of an effective and new biomarker of gene profile is still limited. DEG signatures identification related to patient OS in standard clinical samples may promote the development of molecular drug subtypes and potential therapy targets.…”
Section: Introductionmentioning
confidence: 99%